Chemical constituents and bioactivity studies on Premna integrifolia Linn - Nordin, Kamarusalihin (2013)
Premna integrifolia known as buas-buas in Malaysia is one of the species of Verbenaceae family. Extraction, fractionation followed by purification of P. integrifolia afforded seven compounds which consisted of flavone, quinone, ester, plant sterols and diterpene. The structures were elucidated using spectroscopic methods including nuclear magnetic resonance (NMR), mass spectrometry (MS), infrared (IR), and ultraviolet (UV) spectroscopies. Two flavones identified as 5,7-dihydroxy-4'-methoxyflavone and 4',5,7-trihydroxyflavone were isolated from the leaves, while two new compounds named integrifolinone and icetexane-X, together with a mixture of two plant sterols, stigmasta-5,22-dien-3ß-ol and stigmasta-5-en-3ß-ol were obtained from the roots. In addition, an ester 2-(4'-hydroxyphenyl)ethyl dodecanoate was isolated from the barks. Antioxidant screening was carried out on the crude extracts and pure compounds. The ethyl acetate extract of the leaves and hexane extract of the roots were found to have low antioxidant activity, while the pure compound icetexane-X gave the most active radical scavenger, with an SC50 of 30.79 µg/mL compared to vitamin C which showed an SC50 of 12.71 µg/mL. In the antimicrobial assay, all the crude extracts and pure compounds were found to be inactive towards all the tested bacteria (Staphylococus aureus, Escherichia coli, Bacillus subtilis and Pseudomonas aeruginosa)